MYOCARDIAL DYSTROPHY IN CAMEL CALVES IN THE UNITED ARAB EMIRATES (FIELD CASES) - Khouly, A. A. El; Abbas, T. A.; Moustafa, T. (Emirates Journal of Food and Agriculture, 2017)
'LIIHUHQWIURPKHDUWPXVFOHG\7KLVVZDVDWWULEXWHGWRVHOHQLXPGHILFLHQF\7KHPRUWDOLW+[ VHYHUH OXQJ HGHPD KDQG YDULRXV GHJUHHV RI FDUGLDF PXVFOH QHFURVLV ZHUH WKH PRVW FRPPRQ SDWKRORJLFDO ILQGLQJV 7KH VHUXP HQ]LQFOXGLQJ FUHDWLQH SKRVSKRNLQDVH &3. /DFWLF GHK/'+ DQG DVSDUWDWH DPLQRWUDQVIHUDVH 67 DQG /DFWLFDFLGZHUHPDUNHGO7KHVHOHQLXPOHYHOLQGLVHDVHGFDVHVZDVOHVVWKDQSSELQ VHUXPOHVVWKDQSSELQOLYHUDQGOHVVWKDQSSELQNLGQH.H(VHOHQLXPFDOYHVFDPHOV ,QWURGXFWLRQ 1XWULWLRQDO PXVFXODU G